EVALUASI METODE LEAN CONSTRUCTION DAN PENJADWALAN CRITICAL CHAIN PROJECT MANAGEMENT (STUDI KASUS REKONSTRUKSI JALAN RUAS GORONTALO-BILUHU BARAT) - Lige, Fifi Nabila; Utiarahman, Arfan; Tuloli, Mohamad Yusuf (Composite Journal, 2023)
Construction project development requires careful planning, but the uncertainty that occurs in the procerss is very diverse. Inefficiencies such as schedule mismatch with the work process in the field must be minimized so that there is no significant waste of costs. Therefore, related parties need to take appropriate steps to identify and evaluate waste so that the planning time and the work process do not differ significantly, so as to reduce waste of costs and provide satisfactory results to the project owner. Thus, it is necessary to conduct research on lean construction mehod and critical chain project management scheduling to know the occurrence of waste so that anything that does not add value can be minimized or even eliminated. Based on the result of interviews, there are 73% value added activity and 27% non-value adding but necessary activity. The critical waste is waiting and unnecessary inventory. The risks that occur are incompatibility of planning designs with the field, delays in materials/tools, damage to materials/tools, work safety, traffic disturbances at the project site, low labor productivity, design change from planners, bad weather, and the COVID-19 pandemic. The estimated total project duration obtained using the Critical Chain Project Management (CCPM) method is 200 days from the initial duration of 266 days.